Screening factors to affect ultrasound-assisted extraction of (poly)phenols from date palm seeds - Lucas-González, Raquel; Viuda-Martos, Manuel; Pérez-Álvarez, José Ángel; Fernández-López, Juana (Frontiers in Chemistry, 2024)
The aim of the current work was aimed to comparedcompare the (poly)phenol profile (free, solubleconjugate and insoluble-bound) and antioxidant activity of date palm seed flour using different extraction methods after (conventional extraction methods (free, soluble conjugate and insoluble bound) and vs. Ultrasound-Assisted Extraction (UAE)), and to determine the most critical variables in the extraction of (poly)phenols thought UAE using the second order design Plackett-Burman design experiment.. Moreover With the Plackett-Burman design, was employed for identify critical variables among seven factors, named, ethanol concentration, liquid: solid ratio (mL / g), sonotrode, amplitude (%), extraction time, extractant pH, and extraction cycle were studied.. After the studied conventional extraction methods, twenty-three compounds were quantified, with protocatechuic acid and catechin being the predominant (poly)phenols. Furthermore, the distribution of (poly)phenols within the cell varied, with glycosylated quercetins and caffeoyl shikimic acids predominantly found in the free forms. Ultrasound-assisted extraction demonstrated efficiency in extracting free and soluble-conjugate (poly)phenols., Hhowever, it showed limitations in extracting insoluble-bound (poly)phenols . HoweverNevertheless, not significant differences were showed among totalsimilar amounts of total (poly)phenols were shown after conventional extraction vs and UAE, 259.69 ± 43.54 and 189.00 ± 3.08 mg / 100 g palm date seed flour, respectively. The Plackett-Burman design revealed liquid-solid ratio as a crucial factor affecting (poly)phenol extraction, with higher ratios yielding better results. Sonotrode choice also influenced extraction efficiency, highlighting that sonotrode with less diameter but higher displacement amplitude showed the best polyphenol recovery and antioxidant activity values. the effect between the maximum power required and the specific volume usedneed for further optimization. The nature of (poly)phenols influenced studied extraction variables differently, emphasizing the complexity of the extraction process. In this line, pure water was sufficient to extract flavan-3-ols after UAE, while ethanol was a crucial factor in extracting quercetin. TOverall, these findings underscore the importance of tailored extraction methods and optimization optimizing extraction methods for maximizing (poly)phenol recovery from date palm seed flour, crucial for various applications in food and health pharmacology industries. Further studies are warranted to explore the interactions between extraction conditions and polyphenol characteristics comprehensively.